(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. La bilateralità “necessaria” e i suoi limiti - 2. Le intese apicali e il generale regime di libertà religiosa - 3. Le intese paraconcordatarie e la delegificazione - 4. La bilateralità “diffusa” e le intese ulteriori - 5. Le differenti bilateralità: una questione di metodo? The "new agreements" State - religious denominations between necessary bilateralism and broad bilateralism ABSTRACT: The paper analyzes the system of sources of Italian ecclesiastical law in its two pillars of agreed rules and unilateral rules. The former are necessarily the result of an agreement between different legal systems because they govern the specific relations between the State and individual religious denominations, that is, between sovereign and autonomous entities in their respective orders. The unilateral rules, on the other hand, fall under State jurisdiction because they aim to regulate rights and procedures relating to the generic freedom of conscience of believers, non-believers and other believers. Nevertheless, even in this second area, bilateralism between the State and ethical-religious groups is increasingly being practiced. However, this must not strictly condition State autonomy in the political order, but must aim to enhance the democratic tool of dialogue, as broad as possible, between institutions and intermediate bodies. The two forms of bilateralism (the necessary one and the broad one) are in fact structured within the processes which grant ethical-religious issues varied legal forms and give rise to different types of sources. It is essential that institutional practice does not artfully confuse the two described "bilateralisms", ending up surreptitiously managing all the heterogeneous and plural ethical-religious factor through a single, heavy and comfortable, bureaucratic method based on mere political discretionality.